177k views
1 vote
Convert y=x^2-4x+5 to vertex form by completing the square

1 Answer

4 votes

Answer:

The vertex form will be:


y(x)=(x-2)^(2)+1

Explanation:

The equation of the vertex form of a quadratic equation is given by:


y(x)=a(x-h)^(2)+k

Where:

a is a coefficient

h is the x value of the vertex

k is the y value of the vertex

To completing the square we just need to add and subtract the square of the term with x divided by 2.


y(x)=x^(2)-4x+((4)/(2))^(2)-((4)/(2))^(2)+5


y(x)=x^(2)-4x+4-4+5


y(x)=(x-2)^(2)-4+5

Finally, the vertex form will be:


y(x)=(x-2)^(2)+1

I hope it helps you!

User Laurent Sarrazin
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.